Debt maturity structure across Europe: Evidence from Greece, Ireland, Italy, Portugal and Spain - Urbano, Hugo Miguel Fernandes (2013)
The purpose of this empirical work is to examine the determinants of corporate debt maturity structure in Greek, Irish, Italian, Portuguese and Spanish listed firms on the main stock index of each country, using panel data methodology. These countries have been highly affected by sovereign debt crisis that developed in Europe, and firms in these countries operate under different environment conditions, which have implications on firms’ debt maturity choice. The sample considers the period 2001-2010, resulting in 855 firm-year observations. We apply the Generalized Method of Moments (GMM) estimation method. We find evidence that firms in these countries adjust their debt maturity ratio to an optimum target level. Opposite to the liquidity risk theory, we find evidence that firms with high liquidity have higher debt maturity ratios. We also provide evidence that firms which synchronize asset and liability maturities have debt with longer maturities. At the country level the results suggest that firms in developed countries have more access to long-term debt. We also find evidence that firms tend to use less long-term debt in countries with high inflation. Firms use more short-term debt when financial sector has a higher dimension. In countries where the legal system is more effective firms use debt with longer maturities. Finally, we observe a slowdown on firms’ debt maturity during the financial crisis. However, these results are statistically insignificant. Overall, the choice of debt maturity structure is determined by both firms-specific and country-specific effects.